2007
DOI: 10.1007/s00266-006-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry of the Normal Human Auricle: A Study of Adult Indian Men

Abstract: The human ear continues to grow throughout life. The lobule contributes the most to the overall elongation of the auricle. This study furnishes the first set of metric data of auricular dimensions for normal Indian males 18 to 70 years of age. In comparison with other ethnic groups, Indian males seem to have the smallest auricular and lobular lengths, although their respective widths are comparable with those of others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 19 publications
5
68
0
2
Order By: Relevance
“…Project had not provided encouraging results (18,19 (20). However this phenomenon was confirmed in previous studies (6,21 (11,16,17 …”
Section: The Mean Age Of All Observers Was 242±34 Years (20-45 Yearmentioning
confidence: 63%
“…Project had not provided encouraging results (18,19 (20). However this phenomenon was confirmed in previous studies (6,21 (11,16,17 …”
Section: The Mean Age Of All Observers Was 242±34 Years (20-45 Yearmentioning
confidence: 63%
“…Previously, Farkas et al 1 reported the most comprehensive study about measurements and general morphology of the auricle and established the auricular growth of normal West German and North American Caucasian population. Subsequently, few studies on this aspect have been undertaken in several ethnic groups [6][7][8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Auricle is one of five main characteristics of the human face and is very influential in determining its appearance. 6 Type of external ear malformations that affect to the facial appearance can be found, among others in oculo-auriculo-vertebral spectrum patients ranged from slightly dysmorphic to absent ears (or anotia: the most severe form of microtia). malformations and or external factors such as trauma, burns, tumors, punctured defects, scars, and inflammation/allergies.…”
Section: Introductionmentioning
confidence: 99%